2017
DOI: 10.1210/en.2017-00263
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin-Deficient Mouseβ-Cells Do Not Fully Mature but Can Be Remedied Through Insulin Replacement by Islet Transplantation

Abstract: Insulin receptor (IR) insufficiency in β-cells leads to impaired insulin secretion and reduced β-cell hyperplasia in response to hyperglycemia. Selective IR deficiency in β-cells in later embryological development may lead to compensatory β-cell hyperplasia. Although these findings suggest insulin signaling on the β-cell is important for β-cell function, they are confounded by loss of signaling by the insulinlike growth factors through the IR. To determine whether insulin itself is necessary for β-cell develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Insulin serves an important role in the balance of blood sugar levels in the human body, whereby insufficiency results in hyperglycemia, DM and DM complications (46). Previous studies have reported that miRNAs can regulate the synthesis and secretion of insulin (47,48) and regulate the blood sugar balance in the human body (49). miRNAs not only promote insulin synthesis and secretion, but also serve a negative regulatory role in insulin synthesis and secretion (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin serves an important role in the balance of blood sugar levels in the human body, whereby insufficiency results in hyperglycemia, DM and DM complications (46). Previous studies have reported that miRNAs can regulate the synthesis and secretion of insulin (47,48) and regulate the blood sugar balance in the human body (49). miRNAs not only promote insulin synthesis and secretion, but also serve a negative regulatory role in insulin synthesis and secretion (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MafA, Ins1, and Ins2 were expressed throughout culture periods, which are involving in β-cells function and insulin secretion (Hang et al, 2014;Nishimura et al, 2015;Ramzy et al, 2017). The Isl1 was also greatly expressed on day 5 which is working on controlling the development of islets by regulating the transcription of β-cells differentiation.…”
Section: Discussionmentioning
confidence: 98%